The Effect of Workload on Nurse Performance in Hospital Inpatient Settings: A Systematic Literature Review - Kurnia, Ai; Karmilah, Karmilah; Khusnul, Najwa; Fatimah, Siti; Intan, Tanti; Ridwan, Heri; Sutresna, Iyos (Inspirasi Foundation, 2024)
Introduction: The rising nurse workload and its impact on performance have become a significant concern in hospital inpatient settings. Increased patient numbers and high Bed Occupancy Rates (BOR) have contributed to greater pressure on nursing staff, potentially affecting the quality of care provided. Objective: The objective of this study was to assess the effect of workload on nurse performance in hospital inpatient settings through a comprehensive review of existing literature. Method: A systematic literature review was conducted, utilizing national and international journals. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) method was applied in four stages: identification (n = 16,816), screening (n = 60), followed by the application of the PICO framework to determine feasibility and relevance, which resulted in 15 articles being included. The literature search involved accessing electronic databases such as Cochrane, PubMed, and Google Scholar. Result: The review of 15 articles revealed that nurse performance is significantly influenced by multiple factors, with high workload being one of the main contributors. Of the 15 articles analyzed, 14 confirmed that high workload is a major challenge nurses face in performing their daily tasks, leading to potential declines in performance. Conclusion: In conclusion, the study confirms that a high workload, especially in hospital inpatient rooms, has a significant negative impact on nurse performance. Addressing workload management through staffing optimization and effective policies is essential to improving the quality of care and ensuring better health outcomes.